Investigation of formation mechanism of Ti3SiC2 by high pressure and high-temperature synthesis. Issue 4 (2nd October 2018) - Li, Xuhai; Xu, Liang; Chen, Qingyun; Cao, Xiuxia; Liu, Lixin; Wang, Yuan; Zhang, Haibin; Meng, Chuanmin; Wu, Qiang
ABSTRACT: In this paper, synthesis of titanium silicon carbide (Ti3 SiC2 ) under high pressure and high-temperature condition has been investigated by using the reactant systems Ti/Si/C, Ti/SiC/TiC, Ti/SiC/C and Ti/TiC/Si. Results reveal that Ti/TiC/Si is unsuited to the synthesis of Ti3 SiC2 under a high pressure of 2.0 GPa, while an elemental mixture of Ti/Si/C is applicable. By the addition of Al, Ti3 SiC2 with 95.8 wt% purity was obtained from elemental mixture with a large excess of silicon. The optimum experimental parameters were determined as Ti/Si/Al/C having the molar ratio of 3:1.5:0.5:1.9, holding at 2.0 GPa and 1300 °C for 60 min.